(untitled) (Revista LIDER, 2020)
The aim of this paper is to analyze the impact in the Mexican firms if Mexico decides to accomplish the next phase in a major integration processes, adopting a united customs with USA and Canada, 20 years from signing the North American Free Trade Agreement (NAFTA), enforced in 1994, in the period when Mexico changed the substitution industrialization model for the import substitution model, resulting of the globalization trend. The regional integration processes phases is emphasized, analyzing if the Mexican firms are prepared or not to accomplish a united customs, forcing them to center their operations on competitive productive processes and improving their internal organization, as well as on innovation and development.